Corrigendum: Effectiveness of myopia control interventions: a systematic review of 12 randomized control trials published between 2019 and 2021 - Lança, Carla (2024)
[Erratum for: Front Public Health. 2023;11:1125000. DOI: 10.3389/fpubh.2023.1125000.]